Pengaruh Konsentrasi Ammonium Sulfat Dan Waktu Pada Fermentasi Pulp Kakao Menjadi Bioetanol Menggunakan Saccharomyces Cerevisiae - Yuthia Aulia Riani; Chairul Chairul; Wisrayetti Wisrayetti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bioethanol is one of renewable alternative energy source that can be used as an alternative fuel. Bioethanol can be produced from plant containing starch, sugar, and cellulose through a process of fermentation. One of material can be potential as bioethanol feedstock is cocoa pulp that has glucose content 8-14%. The aim of this research was studying the effect of ammonium sulfate concentration as nitrogen source and fermentation time to process cocoa pulp fermentation to produce bioethanol. The steps of this research comprise preparation of fermentation medium, making inokulum of yeast Saccaromycess cerevisiae, and fermentation step. This study varied of ammonium sulfate concentration 0 g/l, 1 g/l, 2 g/l, and 3 g/l and fermentation time of 24, 36, 48, 60, 72, 84, and 96 hours at pH 5, temperature of 30oC, and inokulum size 10% (v/v). Bioethanol concentration was analyzed by using alcoholmeter and glucose concentration was analyzed by Nelson Somogyi method. The fermentation result of cocoa pulp with glucose content of 124,234 mg/ml was showed that the highest bioethanol concentration was 7% or 55,251 mg/ml for using ammonium sulfate of 2 g/l and fermentation time of 72 hours.Keywords: Ammonium Sulfate, Bioethanol, Cocoa Pulp, Fermentation, Saccaromycess cerevisiae